Antibiotic export by efflux pumps affects growth of neighboring bacteria. Issue 1 (December 2018) - Wen, Xi; Langevin, Ariel; Dunlop, Mary
Abstract Cell-cell interactions play an important role in bacterial antibiotic resistance. Here, we asked whether neighbor proximity is sufficient to generate single-cell variation in antibiotic resistance due to local differences in antibiotic concentrations. To test this, we focused on multidrug efflux pumps because recent studies have revealed that expression of pumps is heterogeneous across populations. Efflux pumps can export antibiotics, leading to elevated resistance relative to cells with low or no pump expression. In this study, we co-cultured cells with and without AcrAB-TolC pump expression and used single-cell time-lapse microscopy to quantify growth rate as a function of a cell's neighbors. In inhibitory concentrations of chloramphenicol, we found that cells lacking functional efflux pumps (ΔacrB ) grow more slowly when they are surrounded by cells with AcrAB-TolC pumps than when surrounded by ΔacrB cells. To help explain our experimental results, we developed an agent-based mathematical model, which demonstrates the impact of neighbors based on efflux efficiency. Our findings hold true for co-cultures ofEscherichia coli with and without pump expression and also in co-cultures ofE .coli andSalmonella typhumirium . These results show how drug export and local microenvironments play a key role in defining single-cell level antibiotic resistance.